2011
DOI: 10.1111/j.1440-1754.2010.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Father involvement and child well‐being

Abstract: Children's development is influenced by the quantity and quality of father involvement (FI) in their care. High levels of FI are associated with significant and highly desirable outcomes for children and families. In order to foster increased positive FI, dissemination of evidence-based knowledge regarding its importance and value is needed. Evidence summarised here suggests that fathers and mothers alike need to be educated about the fact that positive paternal involvement is highly beneficial to children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 12 publications
5
98
0
10
Order By: Relevance
“…On the other hand, maternal support has been observed to be associated more with academic competence (Martin, Ryan, & Brooks-Gunn, 2010). Moreover, paternal support has been expressed as being most critical in the areas with lower levels of maternal support (Wilson & Prior, 2011). Children's relationships with the father and mother may also have varying impacts on different children due to different parenting styles.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, maternal support has been observed to be associated more with academic competence (Martin, Ryan, & Brooks-Gunn, 2010). Moreover, paternal support has been expressed as being most critical in the areas with lower levels of maternal support (Wilson & Prior, 2011). Children's relationships with the father and mother may also have varying impacts on different children due to different parenting styles.…”
Section: Discussionmentioning
confidence: 99%
“…En los últimos años las pesquisas sobre la política social de la paternidad han ido ganando terreno en la agenda de investigación social (Cabrera & Peters, 2000;Hobson, 2002;O'Brien, 2004;Marsiglio & Roy, 2012), fruto del interés creciente sobre la institucionalización de los modos de articulación entre familia, Estado de bienestar y mercado laboral y de la constatación de que la implicación paterna en el cuidado de los hijos es un factor clave tanto para lograr una mayor igualdad de oportunidades entre mujeres y hombres como para mejorar el nivel de bienestar infantil (Björnberg & Kollind eds, 1996;Fusulier & Marquet, 2007;Wilson & Prior, 2011;Martial, 2012;Flaquer, 2013). En España existe una buena tradición de investigación sobre estas temáticas, que se remonta a años atrás y recientemente se advierte un renovado interés por la cuestión (Meil, 1997(Meil, y 2011Valiente, 1997Valiente, y 2005Alberdi y Escario, 2007;Lapuerta, Baizán & González, 2011;Escobedo, Flaquer & Navarro, 2012;Salazar, 2013).…”
Section: Introductionunclassified
“…Redshaw and Henderson reported that women were more likely to receive antenatal and postnatal care and less likely to have postnatal problems when their husbands were highly engaged during the pregnancy and childbirth periods [15]. In addition, the father's involvement in childrearing has been found to be associated with children's development and wellbeing [16]. Therefore, Ethiopian women's perception of their spouse's involvement in childbirth and childrearing should be strengthened in order to improve maternal and child health and well-being.…”
Section: Discussionmentioning
confidence: 99%